Oral cancer staging established by magnetic resonance imaging - Paiva, Rogério Ribeiro de (2011)
The aim of this study was to compare clinical staging and magnetic resonance imaging (MRI) staging for oral cancer, and to assess inter-observer agreement between oral and medical radiologists. A total of 10 patients diagnosed with oral cancer were assessed before treatment. A head and neck surgeon performed clinical TNM staging. Two medical radiologists and two oral radiologists performed a new staging assessment by interpreting MRI scans, without prior knowledge of the clinical staging. They evaluated the extent of the primary tumor (T), metastasis to regional lymph nodes (N) and grouping by stages. The data were analyzed using the Kappa Index. There was significant agreement (p < 0.05) between the clinical and MRI staging assessments made by one oral radiologist for N stage, and between those made by one medical radiologist for the T and N stages and for the grouping by stages. In the MRI assessment, there was significant agreement among all four observers for both T stage and grouping by stages. For the N stage, there was no significant agreement between one oral radiologist and one medical radiologist or between both medical radiologists. There was significant agreement among the remaining radiologists. There was no agreement between the clinical and MRI staging. These results indicate the importance of using MRI for the diagnosis of oral cancer. Training initiatives and calibration of medical and oral radiologists should be promoted to provide an improved multidisciplinary approach to oral cancer.